1995
DOI: 10.1128/aac.39.10.2210
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of trovafloxacin (CP-99,219), a new quinolone with extended activities against gram-positive pathogens, Streptococcus pneumoniae, and Bacteroides fragilis

Abstract: The interesting in vitro antimicrobial activity and pharmacokinetics of the new quinolone trovafloxacin (CP-99,219) warranted further studies to determine its in vivo efficacy in models of infectious disease. The significance of the pharmacokinetic and in vitro antimicrobial profiles of trovafloxacin was shown through efficacy in a series of animal infection models by employing primarily oral therapy. Against acute infections, trovafloxacin was consistently more effective than temafloxacin, ciprofloxacin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…The reason for the reduced killing of B. fragilis when in combination with VREF is unknown (24); nevertheless, the possibility that enterococci could in some way compromise the efficacy of an antibiotic against other members of a mixed infection only compounds the increasing problem of emerging resistant enterococcal strains (13). In addition to the characteristic shared with other quinolones of maintaining activity against large numbers of static cultures, the relatively high concentrations of trovafloxacin found in the abscesses in the present study and by others (9,26) could also explain the efficacy of the drug in these difficultto-treat infections while other antibiotics fail. Extreme variations were found, however, in the concentrations of trovafloxacin measured in the abscesses at each time point.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The reason for the reduced killing of B. fragilis when in combination with VREF is unknown (24); nevertheless, the possibility that enterococci could in some way compromise the efficacy of an antibiotic against other members of a mixed infection only compounds the increasing problem of emerging resistant enterococcal strains (13). In addition to the characteristic shared with other quinolones of maintaining activity against large numbers of static cultures, the relatively high concentrations of trovafloxacin found in the abscesses in the present study and by others (9,26) could also explain the efficacy of the drug in these difficultto-treat infections while other antibiotics fail. Extreme variations were found, however, in the concentrations of trovafloxacin measured in the abscesses at each time point.…”
Section: Discussionmentioning
confidence: 57%
“…The efficacy of 40-and 100-mg/kg doses of trovafloxacin given thrice daily against established B. fragilis infections has also been reported in other murine models (9,26). Girard et al observed a significantly higher reduction in bacterial counts of both B. fragilis and E. coli with trovafloxacin compared to other antibiotics with similar MICs and similar daily doses.…”
Section: Discussionmentioning
confidence: 91%
“…Based on previously published studies, mice were administered subcutaneous (to the flank skin) or oral (via gavage) therapeutic doses of vancomycin (110 mg/kg administered subcutaneously twice daily) (30, 31) (Novaplus; Hospira, Inc., Lake Forest, IL), daptomycin (50 mg/kg administered subcutaneously daily) (32, 33) (Cubicin; Cubist Pharmaceuticals, Inc., Lexington, MA), linezolid (60 mg/kg administered subcutaneously and orally twice daily) (34) (Zyvox; Pfizer, Inc., New York, NY), clindamycin (100 mg/kg administered orally three times a day) (35,36) (Cleocin phosphate; Pfizer, Inc.), doxycycline (100 mg/kg orally twice daily) (33), and TMP-SMX (320/ 1,600 mg/kg administered orally twice daily) (37,38). Linezolid was used at the same dose for subcutaneous and oral administration because of equivalent bioavailability when given via either route (39).…”
Section: Methodsmentioning
confidence: 99%
“…As discussed above, the fluoroquinolone class of antibiotics appears to have better activity against stationary-phase antibiotics than does the beta-lactam class. Trovafloxacin, the agent used in the present studies, is a drug of this class that has a greater spectrum of activity against gram-positive and anaerobic bacteria than the earlier fluoroquinolone drugs (8).…”
Section: Discussionmentioning
confidence: 99%